2017
DOI: 10.1093/biolre/iox166
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of good- and poor-quality human sperm demonstrates that several proteins are routinely aberrantly regulated

Abstract: Male infertility is a complex condition, and for the most part, all men produce defective spermatozoa, but infertile men have a tendency to produce more. Despite attempts to classify infertility, there is no definitive test. One approach would be to use protein biomarkers; however as yet, we still do not understand proteins that are differentially expressed within defective spermatozoa. As such, we took nine men (fertility status unknown) and used Percoll density gradients to isolate a population of good- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…Furthermore, the presence of these round cells and leukocyte proteins did not interfere in the molecular pathways associated with sperm function [39]. However, while investigating the physiological functions of spermatozoa such as hyperactivation, capacitation and acrosome reaction, the use of pure fractions of normal sperm isolated using double gradient centrifugation or swim-up techniques has been reported [40,41].…”
Section: Proteomic Analysis Using Lc-ms/msmentioning
confidence: 99%
“…Furthermore, the presence of these round cells and leukocyte proteins did not interfere in the molecular pathways associated with sperm function [39]. However, while investigating the physiological functions of spermatozoa such as hyperactivation, capacitation and acrosome reaction, the use of pure fractions of normal sperm isolated using double gradient centrifugation or swim-up techniques has been reported [40,41].…”
Section: Proteomic Analysis Using Lc-ms/msmentioning
confidence: 99%
“…These same enzymes are also responsible for NBT reduction in a biological system, which, much like lucigenin, has been used to conclude that sperm are under “oxidative stress.” The fact that both cytochrome enzymes are more prevalent in sperm with excess of residual cytoplasm also sheds light and offers an alternative explanation to other findings . We and others have shown that sperm with excess residual cytoplasm have very poor motility, morphology, and chromatin compaction. Given this scenario, it is understandable that a “lucigenin” signal (i.e., sperm with excess residual cytoplasm) has been correlated to DNA damage of infertile men, poor capacitation, and poor hyperactivation .…”
Section: Discussionmentioning
confidence: 62%
“…This will allow the implementation of management strategies to maximise PCC rates and in turn, breeding efficiency. To date, several studies have identified fertility biomarker candidate proteins from the spermatozoa of mice, men, livestock production animals, and to a lesser extent, stallions (Baker et al 2005, Novak et al 2010, Park et al 2012, Kwon et al 2015a,b, Swegen et al 2015, Netherton et al 2017. Indeed, at the time of publication of this review, a PubMed search using the terms 'stallion', 'sperm' and 'proteome' produced only six publications.…”
Section: Differential Protein Expressionmentioning
confidence: 98%
“…The abnormal expression of protamines (P1 or P2) leads to aberrant protamine ratios, which are, in turn, associated with defects in spermatogenesis and spermiogenesis leading to conditions such as oligozoospermia, asthenozoospermia or teratozoospermia, particularly in relation to head morphology and diminished sperm penetration assay scores (Aoki et al 2006). Indeed, Netherton et al (2017) reported a 3-fold increase of P2 in poor quality spermatozoa isolated using density gradient centrifugation. In the stallion, three protamine variants have been identified; protamine 1 St1 and protamine 2 variants St2b and St2a (Pirhonen et al 1989).…”
Section: Dna Packagingmentioning
confidence: 99%